Analysing films to rethink the psychology of time - Stenner, Paul; Zittoun, Tania (SAGE Publications, 2025)
This paper contributes to social and cultural psychology by means of a systematic reflection on the notion of time in its togetherness with space as revealed by films. It presents a new theorisation of Mikhail Bakhtin’s concept of the ‘chronotope’ by distinguishing created, creating, and creative types which exist in dynamic relations of mutual presupposition. This new theorisation is then used to guide the thematic decomposition of five films directed by Christopher Nolan (Tenet, Inception, Memento, The Prestige, and Oppenheimer). Each film, with its many minor chronotopes, offers its appreciator a distinctive meditation on the varied ‘shapes’ time can take, including the ways it can become problematic in people’s lives. But taken together the films express a distinctive major chronotope which, we argue, characterises Nolan’s genre more generally. We describe this as a chronotope of permanent liminality because characters and appreciators alike are confronted with paradoxes of constant transition involving multiple temporalities in which created, creating, and creative chrontopes are deliberately mixed. This opens new perspectives on the psychological value of aesthetic experiences, showing how art and life weave into one another thanks to being woven out of one another. Films do not merely entertain us but allow us to entertain the complexity proper to reality viewed, not as a static underlying materiality (about which we form representations) but as a real process of transition composed out of a rich multiplicity of temporal happenings
Keywords: arts; Bakhtin; Film; Christopher Nolan; Time